The relaunch and conclusion of EU-Mercosur trade negotiations through the lens of Brazil and Argentina (2010-2019) - José Victor Ferro (Política Internacional)
In 2019, the EU and Mercosur reached a preliminary agreement on bilateral trade liberalization. While still an agreement in principle, pending official signatures from representatives on both sides, it marked a significant milestone that brought a negotiation process—initiated in 1999—to a close. This article aims to analyze the relaunch of these negotiations, which initially spanned from 1999 to 2004, followed by a pause until 2010, and ultimately concluded in 2019. It examines the positions of Brazilian and Argentinian foreign policies toward EU trade talks, focusing on how each country’s development model and integration strategy shaped their national stance on these negotiations. Our analysis concludes that there were two distinct phases in the negotiation period from the relaunch through to its conclusion.